A Study of Soft Topological Axioms and Soft Compactness by Using Soft Elements - Sujay Goldar; Subhasis Ray (Journal of New Results in Science)
In this article, we study the ordinary topology on the collection of soft elements. Some interesting relations between the ordinary topology on the collection of soft elements and the soft topology are discussed. New definition of soft separation axioms and soft compactness are presented and studied using soft elements.